Effective efforts in resolving international disputes: A review of the principles of international law in the case of the Ligitan and Sipadan Island disputes - Simamora, Yehezkiel Hasiholan (International Law Discourse in Southeast Asia, 2023)
This article discusses effective efforts to resolve international disputes by focusing on reviewing the application of international law principles in the context of the Ligitan and Sipadan Island disputes. This research explores the role of international legal principles, such as the principles of peace, justice and sovereignty, in handling territorial disputes between Indonesia and Malaysia regarding these two strategic islands. Through in-depth analysis of the settlement process, this article identifies concrete efforts that can be considered effective in resolving international disputes, as well as considering the impact of applying international legal principles in achieving just and sustainable solutions. The implications of this research can provide additional insight for stakeholders, international law practitioners, and researchers interested in the context of international dispute resolution, especially in cases involving international legal principles at the regional level.